Pengaruh Work From Home, Work-Life Balance, Stres Kerja, dan Employee Relations Terhadap Kepuasan Kerja Pada Pekerja Yang Sedang Berkuliah - Rosa Damayanti, Mela; Ria Atmaja, Dodi (CV. Lafadz Jaya, 2022)
The purpose of this study is to examine the factors that influence job satisfaction in the context of remote work caused by the pandemic, such as work-life balance, work stress and employee relations for workers who are in college. This study uses a quantitative approach. The method used in this research is a survey method by distributing online questionnaires to Parallel Students of the Faculty of Economics and Business, Esa Unggul University. The questionnaires collected were 150 respondents and to test the research model, this study used SEM Lisrel. The results obtained indicate that work from home has a positive effect on job satisfaction and work-life balance but has a negative effect on work stress. Further results, work-life balance has a positive effect on job satisfaction, but job stress and employee relations do not have a positive effect on job satisfaction. In addition, this study succeeded in proving that work-life balance can mediate work from home on job satisfaction. However, this study found that job stress was not able to mediate work from home on job satisfaction. Work from home is a new breakthrough in work that can increase job satisfaction as a work atmosphere today and even in the future for workers.